FOXO1 overexpression and loss of pSerine256-FOXO1 expression predicts clinical outcome in esophageal adenocarcinomas. Issue 1 (December 2018) - Grupp, Katharina; Uzunoglu, Faik; Melling, Nathaniel; Hofmann, Bianca; El Gammal, Alexander; Grotelüschen, Rainer; Heumann, Asmus; Bellon, Eugen; Reeh, Matthias; Wolters-Eisfeld, Gerrit; Ghabdan, Tarik; Nentwich, Michael; et al.
Abstract The function of Forkhead box O 1 (FOXO1) and pSerine256-FOXO1 immunostaining in esophageal cancer is unclear. To clarify the prognostic role of nuclear FOXO1 and cytoplasmic pSerine256-FOXO1 immunostaining, a tissue microarray containing more than 600 esophageal cancers was analyzed. In non-neoplastic esophageal mucosae, FOXO1 expression was detectable in low and pSerine256-FOXO1 expression in high intensities. Increased FOXO1 and decreased pSerine256-FOXO1 expression were linked to advanced tumor stage and high UICC stage in esophageal adenocarcinomas (EACs) (tumor stage: p = 0.0209 and p < 0.0001; UICC stage: p = 0.0201 and p < 0.0001) and squamous cell carcinomas (ESCCs) (tumor stage: p = 0.0003 and p = 0.0016; UICC stage: p = 0.0026 and p = 0.0326). Additionally, overexpression of FOXO1 and loss of pSerine256-FOXO1 expression predicted shortened survival of patients with EACs (p = 0.0003 and p = 0.0133) but were unrelated to outcome in patients with ESCCs (p = 0.7785 and p = 0.8426). In summary, our study shows that overexpression of nuclear FOXO1 and loss of cytoplasmic pSerine256-FOXO1 expression are associated with poor prognosis in patients with EACs. Thus, evaluation of FOXO1 and pSerine256-FOXO1 protein expression - either alone or in combination with other markers - might be useful for prediction of clinical outcome in patients with EAC.